(Co-)combustion behaviors and products of spent potlining and textile dyeing sludge. (1st July 2019) - Sun, Guang; Zhang, Gang; Liu, Jingyong; Xie, Wuming; Evrendilek, Fatih; Buyukada, Musa
Abstract: Co-combustion performances, ashes, gases and thermodynamics were quantified for spent potlining (SPL) and textile dyeing sludge (TDS) (with)out CaO. During the four decomposition stages of the blends according to the (D)TG experiments, the interaction among Na, Ca, F, Al, and S led to CaAl2 O4, CaF2, and Na2 SO4 which converted inorganic compounds into ash. Increased comprehensive combustion index, and decreased burnout temperature with 50% SPL indicated a better combustion and char burnout, and a shorter combustion process. CaO reduced the F volatilization and increased F − in the residual ash with 10% CaO. NaF was completely converted into CaF2 reducing the toxicity of soluble F − in the residual ash. The predom diagram of NaCaFS using thermal simulations showed the stable existence regions of CaF2 and Na2 SO4 . The changed migration mechanisms of F − and S caused ash compositions to consist of Na2 SO4 and CaF2 for the co-combustions, and of NaF and CaSO4 for the mono-combustions. 10% CaO promoted CaF2, Na2 SO4, CaAl2 O4, and to a lesser extent, Fe2 O3 . The main gases evolved from the co-combustion included HF, SO2, COS, CS2, HCN, NH3, NO, and NO2 . Graphical abstract: Image 1 Highlights: (Co)combustions of spent potlining (SPL) and textile dyeing sludge (TDS) were quantified. Interaction between SPL and TDS promoted ash formation at above 750 °C. CaF2 and Na2 SO4 grew stronger with increased CaO unlike Fe2 O3 . Fluoride was efficiently retained in ash with added CaO. Mineral transformations and ash melting were thermodynamically simulated.